Increasing Dietary Vitamin K Intake Stabilizes Anticoagulation Therapy in Warfarin-Treated Patients with a History of Instability: A 24-week Randomized Controlled Trial (OR36-04-19). (13th June 2019) - Ferland, Guylaine; Chahine, Suzanne; Presse, Nancy; Dube, Marie-Pierre; Nigam, Anil; Blostein, Mark; deDenus, Simon; Perreault, Sylvie; Tardif, Jean-Claude
Abstract: Objectives: Warfarin (W) is a highly prescribed anticoagulant for the treatment and prevention of thromboembolic diseases. However, anticoagulation stability is often a challenge due to the narrow therapeutic range of the drug. In recent years, dietary vitamin K (VK) has emerged as an important modulator of long-term anticoagulation stability. In trials, patients receiving small doses of supplemental VK (100–150 mg/d) spend significantly more time in the therapeutic range (%TTR) and present fewer bleeding and thrombotic complications. Whether similar beneficial effects can be achieved through diet remains unknown. We determined whether increasing dietary VK intake by ≥150 µg/day improves anticoagulation stability of W-treated patients with a history of INR instability. Methods: We conducted a 24-week randomized controlled trial at the Anticoagulation Clinics of the Montreal Heart Institute and the Jewish General Hospital (Montreal). The main inclusion criteria were: 1) be anticoagulated for >6 months with a target international normalized ratio (INR) range of 2.0–3.0 or 2.5–3.5, and 2) present a %TTR <50% in the previous 6 months. Patients randomized to the intervention group (VK) received dietary counsel to increase their VK intake by ≥150 µd/day through specific food choices, recipes and cooking strategies. Patients from the control (C) group received general dietary information of similar intensity. Warfarin therapy was monitored weekly by INR. The primary clinical outcome was anticoagulation stability as defined by %TTR ˃ 70% during weeks 4 through 24. Groups were compared in an intention-to-treat method using the exact Fisher test. Results: In total, 49 patients aged 32–85 years completed the study. Mean (±SEM) %TTR over the assessment period were 67.7 ± 3.4 and 61.4 ± 3.5 for the VK and C groups, respectively (ns). Increasing dietary VK intakes resulted in a greater proportion of patients with %TTR ˃ 70% over the assessment period. Specifically, 14 of the 28 patients (50%) from the VK group met the criteria versus 4 of the 21 patients (19%) from the C group ( P  = 0.026). Conclusions: Increasing VK intake ≥150 µd/day through diet strategies improves anticoagulation stability of W-treated patients with a history of anticoagulation instability. Funding Sources: This study was funded by the CIHR.